The South African personal income tax base, 2011-2018 - Donaldson, Andrew R. (United Nations University World Institute for Development Economics Research, 2023)
Tax administration statistics now provide considerably more complete and reliable measures of South African personal income and its distribution than the available household or other survey sources. However, there are difficulties in using tax data across time, as both policy and reporting changes influence the administrative statistics of income. This paper uses two sets of adjustments to generate a consistent personal income series for the 2011-2018 period: upward adjustments to published statistics on assessed taxpayers to provide estimates consistent with the overall tax base, and adjustments for retirement contribution and medical expense reporting changes in 2013, 2015, and 2017 that affect the calculation of taxable income and income before deductions. About half of all individuals reporting income to the South African Revenue Service are contributors to retirement funds, and just over a quarter qualify for medical scheme or medical expense tax benefits. The resulting adjusted income distribution estimates show that the tax base increased robustly relative to GDP over this period, that income shifted towards older and higher real income taxpayers, and that income inequality increased.
10.35188/UNU-WIDER/2023/351-2
Keywords: Graue Literatur; statistics of income; income distribution; personal income tax